Kartläggning av utbildningsmaterial inom djurskydd för naturbruksprogrammet - Abrahamsson, Hanna (2018)
According to the European Commission, 90 % of the European citizen find animal welfare to be important. Consumers of animal products wants to know about animal welfare so that they can make conscious choices. Unfortunately, the knowledge is too low even if people are interest ed and there are other aspects such as emotions, culture and social status behind what they purchase. The public is becoming more aware of animal welfare and the community interest is increasing. This means that demand for animal welfare education material for natural resource use program at high school level also increases. The aim of this study was to map animal welfare education material for natural resource use program at high school level. This was done by sending emails with questions to teachers who teach animal welfare at high school level. The questions asked was what type of education material the teachers use, how it works and if they had any suggestions for improvement. Results showed that the materials used to the greatest extent was the website and folders, both from the Swedish Board of Agriculture, the Animal Welfare Act and tasks made by teachers. These materials work quite well, but they are not tailored to the target audience according to the informants. The informants identified a need for materials that are easier to read and with explanatory pictures. The results also showed that the clarity of animal welfare in curricula is lacking in natural resource use program. In summary, the materials that are used today have according to the assessment, a scientific base and they can be considered objective. But they are not specifically adapted to serve as education material. Further investigation is proposed about how an education material should be designed and then it may be relevant to develop an animal welfare education material.